The First IEEE/RAS-EMBS International Conference on Biomedical Robotics and Biomechatronics, 2006. BioRob 2006.
DOI: 10.1109/biorob.2006.1639124
|View full text |Cite
|
Sign up to set email alerts
|

Uncalibrated Visual-Servoing of a Dual-Arm Robot for MIS Suturing

Abstract: In minimally invasive surgery small incisions are made in a patient's body. Long thin instruments and an imaging endoscope are inserted through the openings and a surgeon manipulates the tools using visual feedback from the endoscope. The difficulties of performing such surgery are outlined e.g. due to lack of dexterity the motions required can place tremendous strain on a surgeon's joints. This work looks at some of the issues involved in using visual-servoing to tie surgical knots with two robots. The constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Several methods have been proposed, among them the detection of the shaft's geometrical appearance in the image (see [11], [12]), tracking special orientation markers (e.g. gray encoders [6]) or using colored patches [13]. Also specialized devices equipped with LED markers and a projective laser to identify the tool orientation have been proposed [14].…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been proposed, among them the detection of the shaft's geometrical appearance in the image (see [11], [12]), tracking special orientation markers (e.g. gray encoders [6]) or using colored patches [13]. Also specialized devices equipped with LED markers and a projective laser to identify the tool orientation have been proposed [14].…”
Section: Feature Extractionmentioning
confidence: 99%
“…smallscale knots performed under trocar kinematics and original suture material). Hynes et al [6] employed visual servoing in order to command the robot movements, but the desired points have to be selected manually in the images. In [7] and [8] we demonstrated an approach to tie a suture knot autonomously using general purpose laparoscopic instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researchers have presented new looping methods or special devices to improve knot-tying procedures for MIS [1][2][3][4][5][6]. To address the challenge of reliable knot-tying in the context of complex deformation (twist and sag) of suture [7], The authors are with the EECS Department at Case Western Reserve University.…”
Section: Introductionmentioning
confidence: 99%
“…Krupa et al [7] have demonstrated a system that automatically aligns surgical instruments equipped with an additional laserpointer to project an orientation pattern on the surface of the organs. Hynes et al [8] have built a dual-arm system equipped with surgical instruments and a (conventional) stationary stereo camera to evaluate the prospects of visual servoed knot-tying. More recently, Nageotte et al [9] have proposed a method for robot-assisted path following, using a 2D visual servoing scheme and depth estimation with markers applied on the instrument tip.…”
Section: Introductionmentioning
confidence: 99%